Mental health consequences during the initial stage of the 2020 Coronavirus pandemic (COVID-19) in Spain - González-Sanguino, Clara; Ausín, Berta; Castellanos, Miguel Ángel; Saiz, Jesús; López-Gómez, Aída; Ugidos, Carolina; Muñoz, Manuel (Brain, behavior, and immunity, 2020)
•The 18.7% of the sample revealed depressive symptomatology, the 21.6% anxiety and the 15.8% PSTD.•Being older, economic stability and information were negatively related to the symptomatology.•Female, previous diagnoses or Covid-19 symptoms were associated with symptomatology.•Spiritual well-being was a common protector for all symptomatology and the loneliness a predictor. The pandemic caused by Covid-19 has been an unprecedented social and health emergency worldwide. This is the first study in the scientific literature reporting the psychological impact of the Covid-19 outbreak in a sample of the Spanish population. A cross-sectional study was conducted through an online survey of 3480 people. The presence of depression, anxiety and post-traumatic stress disorder (PTSD) was evaluated with screening tests from 14 March. Sociodemographic and Covid-19-related data was collected. Additionally, spiritual well-being, loneliness, social support, discrimination and sense of belonging were assessed. Descriptive analyses were carried out and linear regression models compiled. The 18.7% of the sample revealed depressive, 21.6% anxiety and 15.8% PTSD symptoms. Being in the older age group, having economic stability and the belief that adequate information had been provided about the pandemic were negatively related to depression, anxiety and PTSD. However, female gender, previous diagnoses of mental health problems or neurological disorders, having symptoms associated with the virus, or those with a close relative infected were associated with greater symptomatology in all three variables. Predictive models revealed that the greatest protector for symptomatology was spiritual well-being, while loneliness was the strongest predictor of depression, anxiety and PTSD. The impact on our mental health caused by the pandemic and the measures adopted during the first weeks to deal with it are evident. In addition, it is possible to identify the need of greater psychological support in general and in certain particularly vulnerable groups.